Analisis Pengaruh Tingkat Inflasi Dan Tingkat Bagi Hasil Terhadap Profitabilitas Pada Bank Umum Syariah Di Indonesia - Nita, Destiana Dwi; Ariffin, Muhammad; Nurisniani, Neni (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine the effect of Inflation Rate and Profit Sharing Rate on Sharia Commercial Bank Profitability in Indonesia. The independent variable (independent) in this study is the level of inflation and the level of profit sharing, while profitability is the dependent variable. In this study, researchers used Return on Assets (ROA) as an indicator for profitability. The method used is descriptive method and verification method. The data used are secondary data sourced from Financial Statements that have been published by Bank Muamalat Indonesia, Bank Rakyat Indonesia (BRI) Syariah, Bank Bukopin Syariah, Bank Negara Indonesia (BNI) Syariah, and Bank Central Asia (BCA) Syariah. The data analysis technique used is panel data regression analysis and classic assumption test, because the data used are secondary data and the type of data used is a combination of cross section data and time series data. Data processing techniques using the help of Eviews 9 program. Based on data analysis that has been done using panel data regression and classical assumption tests, it is found that the Inflation Rate has a negative and significant effect on Return on Assets (ROA), this result is evidenced by the significance value of 0,0012 and the regression coefficient shows a figure of -0,0817. Level of Profit Sharing is positive and significant effect, this result is evidenced by the significance value of 0.0000 and the regression coefficient shows a figure of 0,1644. The coefficient of determination (R-square) value is 77,26%. Keywords: Inflation Rate, Profit Sharing Rate, Return on Assets (ROA).